Factors affecting learner success in an ESL self-access programme : a case study - Thanasingam, Santhakumari (2020)
This study evaluates the impact of an online language support programme developed from the self-access component of an earlier blended-scaffolded learning model used to teach English Proficiency to undergraduate students. This online language support programme was designed using data collected from the self-access component of that study which used the Spring-Cycle Curriculum Model (SCBC). The new programme combined the benefits of a consultation mode which offered face-to-face personal support and a self-access mode which enabled students to learn autonomously. A focus group interview and grounded analysis was used to evaluate factors that impacted learner success in the self-access programme. Data from the focus group interview showed that learner readiness and tutor support were the two main factors that impacted the ability of the ESL learner to be successful in this approach to learning. The study confirms findings from other research and highlights the need to consider these two factors in the design of successful self-access programmes.